DIRECT MEASUREMENT OF THE X-RAY TIME-DELAY TRANSFER FUNCTION IN ACTIVE GALACTIC NUCLEI - Legg, E; Miller, L; Turner, T; Giustini, M; Reeves, J; Kraemer, S (2012)
The origin of the observed time lags, in nearby active galactic nuclei (AGNs), between hard and soft X-ray photons is investigated using new XMM-Newton data for the narrow-line SeyfertI galaxy Ark 564 and existing data for 1H0707-495 and NGC4051. These AGNs have highly variable X-ray light curves that contain frequent, high peaks of emission. The averaged light curve of the peaks is directly measured from the time series, and it is shown that (1) peaks occur at the same time, within the measurement uncertainties, at all X-ray energies, and (2) there exists a substantial tail of excess emission at hard X-ray energies, which is delayed with respect to the time of the main peak, and is particularly prominent in Ark 564. Observation (1) rules out that the observed lags are caused by Comptonization time delays and disfavors a simple model of propagating fluctuations on the accretion disk. Observation (2) is consistent with time lags caused by Compton-scattering reverberation from material a few thousand light-seconds from the primary X-ray source. The power spectral density and the frequency-dependent phase lags of the peak light curves are consistent with those of the full time series. There is evidence for non-stationarity in the Ark 564 time series in both the Fourier and peaks analyses. A sharp "negative" lag (variations at hard photon energies lead soft photon energies) observed in Ark 564 appears to be generated by the shape of the hard-band transfer function and does not arise from soft-band reflection of X-rays. These results reinforce the evidence for the existence of X-ray reverberation in typeI AGN, which requires that these AGNs are significantly affected by scattering from circumnuclear material a few tens or hundreds of gravitational radii in extent. © 2012. The American Astronomical Society. All rights reserved.